Development of Traditional Mask Mold as Teaching Tool in Learning of Arts, Culture, and Craftsmanship - Retno Putri, Yuyarti, Dianita Ika (Universitas Negeri Semarang, 2018)
Based on preliminary observation at SDN Kedungane 02 Semarang, learning media in art, culture, and craft lesson subject in the lesson of making a mask was still limited. It was necessary to develop a learning media which supporting thepractice of making a mask.The type of research was Research and Development. The steps consist of potential and problem, data collection, product designing, design validation, design revision, small group product testing, productrevision, large group product testing, product revision, and final product making. The main subject of this research was the students of grade V SDN Kedungpane 02 consists of 39 students. Technical collecting data used both test and non-test techniques. Data analysis technique used percentage descriptive statistic, validity test, reliability test, and N-gain. The results of the research showed: (1) the mask mould product design which was being developed was a traditional mask from Java Island and being adjusted to the level of student development, (2) the result of product feasibility assessment from material expert was 96,4% (very feasible) and media expert was 94,2% (very feasible), (3) the effectiveness of the media was being seen from the responses of students and teachers with the result belong to very good criteria, and there was an moderated improvement in pre test and post test result. Showed by the result of gain test value which was 0,52 and the average of performance assessment value was 88,36. The conclusion of this research was the traditional mask-mould media in the lesson of making a mask at class V of elementary school was feasible to be used and effective in improving the result of student art work.